2007
DOI: 10.1007/s10517-007-0261-1
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of mutations in BRCA1 and BRCA2 genes in ovarian cancer

Abstract: The incidence of mutations in the BRCA1 and BRCA2 genes in the studied sampling of 74 patients with ovarian cancer was 19%. The incidence of mutations in the Russian sampling of patients, formed without consideration for the family history, is one of the highest in European countries. Retrospective analysis showed that 9% patients carrying mutation had no family history of ovarian or breast cancer. The majority of mutations (86%) were detected in BRCA1 gene, where 5382insC mutation predominated (58%). These da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…[ 19 ] In Poland, 21 out of 151 consecutive OC patients accounted for BRCA1/2 mutations (13.9%)[ 20 ] while for 74 Russian patients, the prevalence of the BRCA1/2 mutation was 19%. [ 21 ] In Korea, BRCA1/2 mutations patients with a positive family history of ovarian cancer patients were 13 of 40 (33%) while 23 had no positive family history out of 283 patients (8%). [ 22 ]…”
Section: Genetic Biomarkers For Ovarian Cancermentioning
confidence: 99%
“…[ 19 ] In Poland, 21 out of 151 consecutive OC patients accounted for BRCA1/2 mutations (13.9%)[ 20 ] while for 74 Russian patients, the prevalence of the BRCA1/2 mutation was 19%. [ 21 ] In Korea, BRCA1/2 mutations patients with a positive family history of ovarian cancer patients were 13 of 40 (33%) while 23 had no positive family history out of 283 patients (8%). [ 22 ]…”
Section: Genetic Biomarkers For Ovarian Cancermentioning
confidence: 99%
“…A number of Russian studies indicate that there is a relatively high frequency of the “Jewish” BRCA1 185delAG allele in Russian patients [20, 23, 24, 26]. In contrast to the BRCA1 5382insC mutation, however, this mutation is not dominant and could be better explained by interethnic marriages.…”
Section: Epidemiology Of the Brca1 Brca2 Chek2 And Nbs1 Mutationsmentioning
confidence: 99%
“…It has been shown that non-founder mutations are much rarer in Russia than in Europe and North America [12, 18–20, 23, 33]. Given the rapidly falling costs of DNA analysis, it is logical to expect an increase in the use of BRCA1 sequencing even for the patients with low probability of cancer genetic predisposition.…”
Section: Epidemiology Of the Brca1 Brca2 Chek2 And Nbs1 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Belgium, de Leeneer et al tested 193 sporadic cases of breast and ovarian cancer for BRCA1/2, finding 3 carriers among 7 women with both breast and ovarian cancer (42.9%) but none among 6 patients with OC only [50]. In Poland, BRCA1/2 mutations were identified in 21 out of 151 consecutive OC patients (13.9%) [51], while in a sample of 74 Russian patients, the prevalence was as high as 19% [52]. In Korean OC patients, BRCA1/2 mutations were detected in 13 of 40 (33%) reporting a strong family history and in 23 of 283 (8%) without significant family history [53].…”
Section: Clinicopathological Features Of Brca-associated Ovarian Cmentioning
confidence: 99%